1985
DOI: 10.1002/path.1711470203
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tumour cells in malignant fibrous histiocytomas and other soft tissue tumours in comparison with malignant histiocytes. I. Immunohistochemical study on paraffin sections

Abstract: We have studied the possible origin of histiocytic cells, present in fibrous histiocytomas (MFH) by using immunohistochemistry to demonstrate lysozyme, alpha 1-antitrypsin, alpha 1-antichymotrypsin and receptors for peanut and soy bean agglutinin in tumour cells of MFH compared with their presence in tumour cells of malignant histiocytosis (MH) ('true' histiocytic lymphoma, 'true' histiocytic sarcoma). We included in this study a number of other soft tissue tumours (STT). Lysozyme was detected in half of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 31 publications
(2 reference statements)
1
37
0
Order By: Relevance
“…However, they were also reactive with fibrosarcoma and/or fibroblast cell lines and were thus considered no longer specific for monocyte/macrophages (20,48). All MFH cell lines showed immunohistochemical characteristics very similar to those of fibrosarcoma and fibroblast cell lines (48) as reported by several researchers (5,39,40,55). Positive reaction to the antibodies against type I collagen and prolyl hydroxylase, the enzyme which catalyzes the 4-hydroxylation of proline residues in procollagen, indicates that MFH cells have the capacity to produce collagen (48).…”
Section: Immunohistochemistry Of Malignant Fibrous Histiocytomasupporting
confidence: 67%
See 1 more Smart Citation
“…However, they were also reactive with fibrosarcoma and/or fibroblast cell lines and were thus considered no longer specific for monocyte/macrophages (20,48). All MFH cell lines showed immunohistochemical characteristics very similar to those of fibrosarcoma and fibroblast cell lines (48) as reported by several researchers (5,39,40,55). Positive reaction to the antibodies against type I collagen and prolyl hydroxylase, the enzyme which catalyzes the 4-hydroxylation of proline residues in procollagen, indicates that MFH cells have the capacity to produce collagen (48).…”
Section: Immunohistochemistry Of Malignant Fibrous Histiocytomasupporting
confidence: 67%
“…Early immunohistochemical studies indicated the histiocytic origin of MFH because many histiocytic markers were demonstrated in at least some cases of MFH (6,8,11,23,31). In recent studies, however, most histiocyte markers such as alpha-l -antitrypsin, alpha-1 -antichymotrypsin, lysozyme, Fc receptor, and S100-protein were found to be not specific for macrophages but recognized on various nonhistiocytic cells (40,55). This notion is also true for some monoclonal antibodies incorporated into CD classification.…”
Section: Immunohistochemistry Of Malignant Fibrous Histiocytomamentioning
confidence: 99%
“…These tumors are believed to arise from undifferentiated mesenchymal cells rather than histiocytes, and typically show pleomorphic and storiform growth patterns. 75,76 Enzymatic and immunophenotypic studies 77,78 have shown that the neoplastic cells in these tumors are negative for histiocytic markers but may contain numerous reactive histiocytes. Despite these subtle morphologic and immunophenotypic differences, clinical history may be the only means of differentiating HS from a metastatic soft-tissue malignancy involving lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of immunohistochemistry and the accessibility of numerous monoclonal antibodies directed against various structural proteins of specific cell types, the phenotype of this tumor was shown to be more closely aligned with a fibroblast than a histiocyte. [3][4][5][6] Furthermore, many, but not all, lesions labeled as 'malignant fibrous histiocytoma' could, upon close scrutiny, be subclassified as lineage-specific sarcomas, an observation that led some to question the existence of MFH as a distinct entity. 7 The extent to which such lesions can be subclassified as sarcomas of alternative type is, in large part, dependent on definitional criteria and the number of ancillary studies a pathologist is willing to bring to bear on the evaluation of a pleomorphic sarcoma.…”
mentioning
confidence: 99%